Resource Allocation for Long Range Wide-Area Network - Lima, Eduardo; Cerqueira, Eduardo; Oliveira, Helder (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2023)
People in smart cities tend to be constantly connected, and wireless connection technologies have become necessary in their routines. The Long Range Wide-Area Network protocol provides a resource allocation mechanism called Adaptive Data Rate that allocates the transmission parameters to increase scalability and reduce the devices’ power consumption. However, ADR prioritizes scalability at the cost of low reliability. In this paper, we propose the PRA and APRA resource allocation mechanisms. Both aims to hierarchy ensure better performance for devices in Long Range networks. While PRA aims to reduce transmission delay and power consumption, APRA reduces packet loss and power consumption while increasing the devices’ battery life. The results showed that the PRA mechanism reduced the ToA and power consumption of high-priority devices by up to 85%. APRA increased up to 5% in packet delivery and 85% in energy savings. Furthermore, APRA’s transmission power allocation mechanism has increased the device’s battery life by up to 28 years.